Revised Series of State Domestic Product 1960-61 To 1966-67 Gujarat State (Methods of Computation) - Planning Commission (Planning Commission, 1960)
After the bifurcation of the Bombay State in the year 1960, the estimates of the State Domestic Product (SDP) of Gujarat State are being prepared by the Bureau of Economics and Statistics, Gujarat State (SSB). 2. In the initial years, the estimates were prepared by adopting the method evolved by the Bombay Bureau. By 1964, important new data in the shape of the results of the 1961 Population Census and Annual Survey of Industries had become available. the Gujarat Bureau had in this period conducted a few type studies, results in respect of which augmented the available information. Moreover
Bureau of Economics and Statistics Government of Gujarat